Non-Melanoma Skin Cancers at Sites of Previous Frostbite: Case Report and Review - Khalel Imanbayev; Abay Makishev; Murat Zhagiparov; Pauline McLoone (Karger Publishers, 2018)
The association between ultraviolet radiation exposure and skin cancer is well established. Limited studies have reported an association between frostbite and the development of non-melanoma skin cancer but evidence for a proven link is insufficient and possible carcinogenic mechanisms have not been fully explored. In this report, 3 cases of non-melanoma skin cancer (1 case of basal cell carcinoma and 2 cases of squamous cell carcinoma of the skin) which developed at a site of previous frostbite caused by exposure to extremely cold temperatures in Astana, the capital city of Kazakhstan, are described.